2009
DOI: 10.1038/embor.2009.152
|View full text |Cite
|
Sign up to set email alerts
|

Induction of RNA‐directed DNA methylation upon decondensation of constitutive heterochromatin

Abstract: Centromeric constitutive heterochromatin is marked by DNA methylation and dimethylated histone H3 Lys 9 (H3K9me2) in Arabidopsis. RNA-directed DNA methylation (RdDM) is a process that uses 24-nucleotide (nt) small interfering RNAs (siRNAs) to induce de novo methylation to its homologous DNA sequences. Despite the presence of centromeric 24-nt siRNAs, mutations in genes required for RdDM do not appreciably influence the methylation of centromeric repeats. The mechanism by which constitutive heterochromatin is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
165
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(186 citation statements)
references
References 28 publications
20
165
0
1
Order By: Relevance
“…Total RNA from 2-wk-old leaves or mature pollen of A. thaliana WT (Col-0) plants was isolated using an RNeasy Plant Mini Kit (Qiagen) as previously described (9). FACS-sorted vegetative cell nuclei (9,28) were directly collected into TRIzol LS Reagent (Life Technologies), and total RNA was isolated according to the manufacturer's protocol. RNA samples were treated with DNase (Thermo Scientific) and precipitated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA from 2-wk-old leaves or mature pollen of A. thaliana WT (Col-0) plants was isolated using an RNeasy Plant Mini Kit (Qiagen) as previously described (9). FACS-sorted vegetative cell nuclei (9,28) were directly collected into TRIzol LS Reagent (Life Technologies), and total RNA was isolated according to the manufacturer's protocol. RNA samples were treated with DNase (Thermo Scientific) and precipitated.…”
Section: Methodsmentioning
confidence: 99%
“…Active rRNA genes transcribed in the nucleolus are demethylated at promoter CG sites in the 5′ external transcribed spacer (ETS) region, whereas silent nucleoplasmic copies are heavily methylated, and loss-of-function met1 DNA methyltransferase mutant alleles disrupt rRNA gene silencing (24). To test whether the expression of full-set rRNA variants in pollen vegetative cells correlates with rDNA demethylation, we analyzed previously published methylome data (27) derived from purified sperm and vegetative cell nuclei by fluorescence-activated cell sorting (FACS) (9,28) (Fig. 5G).…”
Section: Cdc48a-mediated Centromeric Heterochromatin Decondensationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in the vegetative nucleus of the pollen grain, where the level of DDM1 protein is particularly low, TEs are reactivated, producing a pattern of siRNA accumulation similar to that seen in ddm1 (Slotkin et al, 2009). These siRNAs are then transported by still unknown mechanisms to the two sperm cells (Slotkin et al, 2009) where they presumably participate in either RdDM or post-transcriptional silencing depending on their size (Schoft et al, 2009;Slotkin et al, 2009). Like other transcripts produced in pollen (Bayer et al, 2009), some or all of these siRNAs could also be carried over to the zygote and the endosperm, where they would exert functions similar to those postulated in sperm cells (Figure 2a).…”
Section: Transgenerational Inheritance Of Dna Methylation Patternsmentioning
confidence: 99%
“…During male gametogenesis, the pollen vegetative cell nucleus undergoes heterochromatin decondenzation coupled with active removal of CenH3. 28 Merai and colleagues showed that the AAA-ATPase chaperone CDC48A is required for the unloading of sumoylated CenH3, chromatin decondenzation and global activation of silent rRNA genes. As the cdc48a allele is rarely paternally transmitted due to defective pollen tube formation, the authors suggested that the bulk rRNA gene activation may be essential to meet the increased metabolic demand during pollen tube growth.…”
Section: Organized Genome In An Organized Nucleusmentioning
confidence: 99%